Kesulitan Belajar Siswa dan Penanganannya pada Pembelajaran Matematika SD - Alisnaini, Ahmad Farhan; Pribadi, Chquita Azura; Khoironi, Dwi Rahmat; Ibrohim, M.; Azilla, Marsya Deva; Hikmah, Nurul (ALSYS, 2023)
One of the subjects that most students experience problems and find it difficult to understand the concepts is mathematics. The task of a teacher is not only to transfer knowledge or convey learning knowledge to students in the classroom. Meanwhile, most of the students explained that subjects related to calculations were subjects that were difficult to understand. The aim is to find out strategies for dealing with learning difficulties in mathematics at the elementary school level. The writing of this article uses a qualitative type. The results of this study are that learning difficulties in mathematics can be caused by internal factors, including study habits, students' attitudes and motivation, students' interest in learning, and sensory abilities. While the description of external factors, including learning facilities, the relationship between students and teachers, and teaching methods used by educators. The conclusion is the way of handling students' mathematics learning difficulties at the elementary school level, including blended learning is used, self-resilience curriculum is implemented by well, using IT is optimized in the learning process, additional learning-based mathematics remedial is given to students, and students' learning difficulties in mathematics are diagnosed as early as possible.